Penciptaan Busana Pesta dengan Sumber Ide Bunga Sepatu - Norhayati, Vika; Wahyuningsih, Urip (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
The aim of the research is to find out the process of creating evening party clothing designs and the process of making them using the source of shoe flower ideas. This research method uses the Double Diamond Design Process, which is divided into 4 stages, including discover, define, develop, deliver. The discover stage is an exploration of the theme in the form of a moodboard featuring hibiscus flowers and evening party fashion designs. At the define stage, the resulting moodboard is then developed into 8 designs. The develop stage is choosing 2 designs to be realized according to the source of the idea using construction pattern and draping techniques. The design is realized using medium size dressfoam. The deliver stage is the process of making detailed shoe flower decorations which are taken from the shape of a flower crown by cutting the staples according to the pattern, pressing them with satin or organza fabric to make flower crown strands and decorating them with sequins and arranging the lace on the dress which has been given sequins and then stitching a trace. . The results of the research are party clothing using construction and draping techniques. making decorations using manipulating flower fabric and manipulating shasiko. Decorative details are applied according to design principles, namely center of interest and proportion.